STAT3‐mediated gene expression in colorectal cancer cells‐derived cancer stem‐like tumorspheres. Issue 4 (9th September 2020) - Lin, Hua‐Ching; Ho, Ai‐Sheng; Huang, Hsin‐Hung; Yang, Bi‐Ling; Shih, Bin‐Bin; Lin, Hsin‐Chi; Yeh, Chun; Hsu, Chung‐Te; Cheng, Chun‐Chia
Abstract: STAT3 is a transcriptional factor involved in tumorigenesis and the initiation of cancer stemness property. However, the STAT3‐downstream regulatory gene expressions in the formation of colorectal cancer (CRC)‐derived tumorsphere is obscure. In this study, RNAseq was used to uncover the potential genes involved in the formation of colorectal HCT116‐ and HT29‐derived stem‐like tumorspheres, whereas HCT116 and HT29 overexpressed CD133. Furthermore, STAT3 was knockdowned and analyzed consequently by RNAseq for picking up the STAT3‐mediated genes associated with tumorspheres formation. Then, quantitative polymerase chain reaction was used for validating the expressions of selected driver genes in epidermal growth factor (EGF) treated‐ and in STAT3‐knockdowned HT29 cells. We found that 654 genes and 646 genes were upregulated in HCT116‐ and HT29‐derived tumorspheres, respectively. There were 103 genes simultaneously increased in both CRC tumorspheres, including, STAT3 selected as a driver gene by NetworkAnalyst (https://www.networkanalyst.ca/ ). Moreover, there were 139 genes downregulated in HT29shSTAT3 cells compared to HT29shLuc cells, 12 of the genes were overlapped with the overexpressed 103 genes from tumorspheres, including, NDRG1, ALDOC, BHLHE40, ATF3, C6orf223, JUND, ERRFI1, HK2, ITPKA, PLOD2, IDI1, and S100A14 . Among them, BHLHE40, ATF3, ERRFI1, ITPKA, and S100A14 were validated and induced by EGF treatment, that were, otherwise, decreased in HT29shSTAT3 cells. We found and validated that STAT3 mediated the formation of CRC stemness tumorspheres, and STAT3‐downstram BHLHE40, ATF3, ERRFI1, ITPKA, and S100A14 may be involved in the stemness property.